Study On Dynamic Mechanical Properties Of Pultruded Kenaf Fiber Reinforced Composites. - Md Akil, Hazizan; Mohamad Mazuki, Adlan Akram; Safiee, Sahnizam; Mohd Ishak, Zainal Arifin; Abu Bakar, Azhar (2010)
This paper reports the dynamic mechanical properties of pultruded kenaf fiber reinforced composites.